Sistem Informasi Administrasi Pada Madrasah Ibtidaiyah Rare Muchtary - Junaidi, Muh. Lutfi; Sugiartawan, Putu (INFOTEKS (Information Technology, Computer and Sciences), 2020)
Computer technology is currently widely used in the business world and even in the world of education today many are applying the use of this computer technology. Without using a computer, a job will waste a lot of time, energy, and thought. In an effort to improve the quality of human resources (HR) and the smooth running of the administrative process, especially in the administrative payment system, speed and accuracy are needed in processing so that the student guardian does not have to wait too long in the payment process. MI Rare Muchtary is a Madrasah Ibtidaiyah school under the auspices of the SPMAA Foundation. Administrative payments are still using the manual method by providing a receipt as proof of payment and then recording in the payment receipt report so that it is prone to errors by officers. Both in recording payment data and in collecting administrative payment data to be used as financial reports, considering that sometimes officers often forget to make receipts/proof of payment. Based on this background, an administrative payment information system is designed which will then be used as a study. a case from a practical work report with the title